THE EFFECTIVENESS OF WATER SPINACH (Ipomea aquatica) IN CONTROLLING THE LEVEL OF SILVER (Ag) IN PHOTOGRAPHIC PROCESSING WASTE LIQUID - Yusriani Sapta Dewi (FT-USNI, 2024)
One of the most hazardous environmental pollutants that existed is silver liquid waste produced in photographic processing. Some types of water plants are believed to be able to absorb organic, inorganic, and other chemical compounds contained in liquid waste, water spinach (Ipoemea aquatica) being one of them. This study aimed to determine the effectiveness of water spinach (Ipoemea aquatica) in controlling silver liquid waste (Ag) contamination in water. The research design used was randomized block design. The data was then analyzed using a particular formula. The results of the study showed that after 15 days of treatment, water spinach (Ipoemea aquatica) was found to be effective in significantly reducing temperature and level of silver (Ag), but not the pH of the waste liquid. The highest effectiveness was observed when fifteen water spinach (Ipoemea aquatica) plants were used; temperature fell 17.90% (1.60% from the control value; and the level of silver (Ag) fell 5.30%